Model Strategi Pemasaran Dalam Menghadapi Persaingan Di Ayam Geprek Firdaus Wates Kabupaten Kediri - Robby Pradika Putra; Zaenul Muttaqien; Kukuh Hardianto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Firdaus Wates geprek chicken, Kediri Regency is one of the eating places whose main menu is geprek chicken which was founded by Mr. Tegar Firdaus in 2020. This research aims to find out the marketing strategy model used and the obstacles faced by Firdaus Wates geprek chicken, Kediri Regency in facing competition . This research uses qualitative research with a descriptive approach to obtain data. The number of research subjects was determined using a purposive sampling technique of 9 people. The research results show that the marketing strategy model in facing competition in Firdaus Wates geprek chicken, Kediri Regency in terms of products sold is varied, product prices are cheaper than similar businesses, the location is located in an easily accessible location and utilizes social media Instagram and Gojek as promotional media. Apart from that, they provide a promotion for free reffil rice for eating on the spot, wing packages get 2 wings and free wifi. The obstacles faced are the large number of similar business competitors in Wates District, Kediri Regency, the Firdaus fried chicken business is still relatively new compared to similar competitors and the lack of employees.